Una parola muta tra filosofia e letteratura. Considerazioni su un paradosso - D’Aurizio, Claudio (Itinerari, 2024)
In his Mute Speech (1998), Rancière states that literature could be seen as a practice to produce a ‘mute speech’ that has risen from the ashes of classical representation thanks to an epistemological and methodological shift inaugurated by Romanticism. Thus, the paper proposes to consider other philosophical theories to highlight the constancy of this idea of a ‘silent speech’ in the relationship between philosophy, literature, and art. Firstly, the article considers Benjamin’s metaphysics of language and his declaration about silence as a goal for the writer. Secondly, the article addresses Adorno and his conception of a mute language of works of art. Finally, the article investigates the ‘absence of work’ and the ‘thought of the outside’ in Foucault’s thought, also mentioning Deleuze and Blanchot’s considerations, to show the presence of this mute speech in the French philosophical production of the second half of the 20th century.